Intelligence-driven power quality monitoring - Hakimie H.; Ramachandaramurthy V.K.; Mukerjee R.N. (2023)
Power quality is an issue that needs continual attention and have increasingly been used as the key indicator for benchmarking of the true performance of many utilities in the world. Since quality of voltage holds significant importance in the functionality of any power network, monitoring of voltage quality has become a major area of investigation. The extreme financial burden required may not be favourable to provide measurements at each bus and line in a network in both transmission and distribution levels. However, to decide on the remedial measures, it is imperative to identify the type and the location of the fault in a power system. In this paper, an overview of the intelligence-driven power quality monitoring system is described. The intelligence-driven monitoring system is used to enhance system observability through pseudo-measurement data generation. Investigation and simulation were performed on a regional network. Subsequently, the type of fault and the probable location of fault whether it is in transmission or distribution level leading to the degradation of quality were identified. 2005 IEEE.